Auxological and endocrine findings in narcolepsy type 1: seventeen-year follow-up from a pediatric endocrinology center - Casale, Sara; Assirelli, Valentina; Pizza, Fabio; Balsamo, Antonio; Gennari, Monia; Pession, Andrea; Plazzi, Giuseppe; Cassio, Alessandra (Frontiers in Endocrinology, 2023)
Narcolepsy Type 1 (NT1) is a rare hypersomnia of central origin linked to hypocretin deficiency, most frequently arising at pediatric age. NT1 could be associated with endocrine comorbidities involving the neuroendocrine axis, predominantly obesity and Central Precocious Puberty (CPP). The primary aim of this study is the evaluation of endocrine and auxological parameters at diagnosis and during follow-up in patients with NT1, treated with Sodium Oxybate (SO) or not. We retrospectively evaluated auxological, biochemical and radiological parameters of 112 patients referred to our Center between 2004-2022. Our study confirms an increased frequency of CPP and obesity in patients with NT1. At first evaluation, obesity was found in 31.3% of patients, while overweight was found in 25.0%. A diagnosis of CPP was made in 19.6% of patients. Interestingly, this group showed a significantly lower level of CSF-hypocretin (hrct-1) at diagnosis compared to others. We found an improvement in BMI SDS in the SO-treated group compared to untreated patients, and this trend persisted also at 36 months of follow-up (0.0 ± 1.3 vs 1.3 ± 0.4; p<0.03). Sixty-three patients reached their final height, with a median-SDS of 0.6 ± 1.1 in boys and 0.2 ± 1.2 in girls. To our knowledge, these are the first results regarding the final height in a large series of pediatric patients with NT1, with normal range of IGF1-SDS levels and stature SDS.